Angiotensin-converting enzyme gene 2350 G/A polymorphism and susceptibility to atrial fibrillation in Han Chinese patients with essential hypertension (Clinics, 2013)
OBJECTIVE: The angiotensin-converting enzyme gene is one of the most studied candidate genes related to atrial fibrillation. Among the polymorphisms of the angiotensin-converting enzyme gene, the 2350 G/A polymorphism (rs4343) is known to have the most significant effects on the plasma angiotensin-converting enzyme concentration. The aim of the present study was to investigate the association of the angiotensin-converting enzyme 2350 G/A polymorphism with atrial fibrillation in Han Chinese patients with essential hypertension. METHODS: A total of 169 hypertensive patients were eligible for this study. Patients with atrial fibrillation (n = 75) were allocated to the atrial fibrillation group, and 94 subjects without atrial fibrillation were allocated to the control group. The PCR-based restriction fragment length polymorphism technique was used to assess the genotype frequencies. RESULTS: The distributions of the angiotensin-converting enzyme 2350 G/A genotypes (GG, GA, and AA, respectively) were 40.43%, 41.49%, and 18.08% in the controls and 18.67%, 46.67%, and 34.66% in the atrial fibrillation subjects (p = 0.037). The frequency of the A allele in the atrial fibrillation group was significantly greater than in the control group (58.00% vs. 38.83%, p = 0.0007). Compared with the wild-type GG genotype, the GA and AA genotypes had an increased risk for atrial fibrillation. Additionally, atrial fibrillation patients with the AA genotype had greater left atrial dimensions than the patients with the GG or GA genotypes (p